Optimization of EPQ Models for Deteriorating Items with Time-Dependent Demand - Prasad, Rajendra (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In this research article, I have thoroughly described the topic “Optimization of EPQ Models for Deteriorating Items with Time-Dependent Demand.” This study focuses on enhancing the Economic Production Quantity (EPQ) model to address challenges related to deteriorating items and time-dependent demand patterns. Traditional EPQ models assume constant demand and ignore the effects of product deterioration and fluctuations in demand over time, leading to inefficiencies in inventory management. This research integrates time-varying demand, such as seasonal or market-driven changes, and product deterioration, which includes factors like spoilage or obsolescence. By incorporating these elements, the model aims to optimize production cycles, minimize waste, and improve cost-effectiveness. The study uses mathematical modeling, numerical analysis, and sensitivity testing to derive a more accurate inventory strategy, tailored for industries dealing with perishable or time-sensitive goods, such as healthcare, retail, and food sectors. Key findings indicate that optimizing production quantities based on time-dependent demand and deterioration rates can reduce total inventory costs by 12-18%. The model proves particularly beneficial for products with high seasonality or significant deterioration, offering cost savings through better alignment of production cycles with demand fluctuations. However, the study also highlights critical trade-offs, including balancing production frequency and holding costs, and emphasizes the importance of accurate demand forecasting and flexible production systems. The results demonstrate the practical advantages of applying this enhanced EPQ model to real-world supply chains, improving overall operational efficiency and responsiveness to changing market conditions.